Stand-alone Photovoltaic System with Three Energy Processing Stages - Costa, Levy F.; Torrico-Bascopé, René P. (Eletrônica de Potência, 2011)
A circuit configuration of low power stand-alone photovoltaic (PV) system adequate to supply residences located in isolated areas is proposed in this paper. The system consists of the association of three converters to process the energy generated by the PV panels. The proposed system is composed by a charge controller, a modified SEPIC (Single-Ended Primary Inductance Converter) topology and a full-bridge inverter with wide range of output voltage. Theoretical analysis of each stage and experimental results of the complete system is presented for a 500W prototype.